A Review on mobile SMS Spam filtering techniques - Abdulhamid, Shafi'i Muhammad; Abd Latiff, Muhammad Shafie; Chiroma, Haruna; Osho, Oluwafemi; Abdul-Salaam, Gaddafi; Abubakar, Adamu; Herawan, Tutut (Institute of Electrical and Electronics Engineers Inc., 2017)
Under short messaging service (SMS) spam is understood the unsolicited or undesired messages received on mobile phones. These SMS spams constitute a veritable nuisance to the mobile subscribers. This marketing practice also worries service providers in view of the fact that it upsets their clients or even causes them lose subscribers. By way of mitigating this practice, researchers have proposed several solutions for the detection and filtering of SMS spams. In this paper, we present a review of the currently available methods, challenges, and future research directions on spam detection techniques, filtering, and mitigation of mobile SMS spams. The existing research literature is critically reviewed and analyzed. The most popular techniques for SMS spam detection, filtering, and mitigation are compared, including the used data sets, their findings, and limitations, and the future research directions are discussed. This review is designed to assist expert researchers to identify open areas that need further improvement.